Distinctive Gene Expression Profiles and Effectors Consistent With Host Specificity in Two Formae Speciales of Marssonina brunnea - Ren, Fei; Yan, Dong-Hui; Wu, Guanghua; Sun, Xiaoming; Song, Xiaoyu; Li, Ruhua (Frontiers in Microbiology, 2020)
The knowledge on host-specificity of pathogen underlaying interaction is becoming an urgent necessary for global warming. In this study, the gene expression profile and the role of effector in host-specificity were integrally characterized with two formae speciales multigermtubi and monogermtubi of a hemibiotrophic pathogen Marssonina brunnea when their infecting respective susceptible poplar hosts. With functional genome comparison referring to a de novo transcriptome of M. brunnea and Pathogen-Host Interaction (PHI) database function annotations, the multigermtubi strain resorted to abundantly significantly differentially expressed unigenes (DEGs) (more than 40%) in colonizing initial invasion stage and in necrotrophic stage. The monogermtubi strain induced much less DEG (less than 10%) in initial invasion stage but abruptly increased to more than 80% DEGs in necrotrophic stage. Both strains induced the least DEGs in biotrophic stage. The orthologs of effector genes Ecp6, PemG1, XEG1, ACE1 and Mg3LysM were foundto be specific with forma specialis depending on infecting stages. Some unigenes homologue to carbohydrate lytic enzyme genes, especially pectate lyases, were notably induced with multigermtubi forma specialis infection, and not expressed in earlier infection stage with monogermtubi forma specialis. The extraordinary difference in functional genome level to the two formae speciales of M. brunnea could be fundamental to their host-specificity determinant and evolution. This study also firstly provided the fungal transcriptome of monogermtubi forma specialis for M. brunnea.